The Asp1 pyrophosphatase from S. pombe hosts a [2Fe-2S](2+) cluster in vivo - Rosenbach, Hannah (J Biol Inorg Chem, 2021)
The Schizosaccharomyces pombe Asp1 protein is a bifunctional kinase/pyrophosphatase that belongs to the highly conserved eukaryotic diphosphoinositol pentakisphosphate kinase PPIP5K/Vip1 family. The N-terminal Asp1 kinase domain generates specific high-energy inositol pyrophosphate (IPP) molecules, which are hydrolyzed by the C-terminal Asp1 pyrophosphatase domain (Asp1(365−920)). Thus, Asp1 activities regulate the intracellular level of a specific class of IPP molecules, which control a wide number of biological processes ranging from cell morphogenesis to chromosome transmission. Recently, it was shown that chemical reconstitution of Asp1(371−920) leads to the formation of a [2Fe-2S] cluster; however, the biological relevance of the cofactor remained under debate. In this study, we provide evidence for the presence of the Fe–S cluster in Asp1(365−920) inside the cell. However, we show that the Fe–S cluster does not influence Asp1 pyrophosphatase activity in vitro or in vivo. Characterization of the as-isolated protein by electronic absorption spectroscopy, mass spectrometry, and X-ray absorption spectroscopy is consistent with the presence of a [2Fe-2S](2+) cluster in the enzyme. Furthermore, we have identified the cysteine ligands of the cluster. Overall, our work reveals that Asp1 contains an Fe–S cluster in vivo that is not involved in its pyrophosphatase activity. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00775-020-01840-w.